DETERMINATION OF THE PLACE OF ACADEMIC RESPONSIBILITY IN THE GENERAL SYSTEM OF LEGAL RESPONSIBILITY - Остапенко, Людмила Анатоліївна; Рудик, Вікторія Анатоліївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: the article examines the issue of the content of academic responsibility as a way of ensuring academic virtuous of its place in the general system of legal responsibility. The article is focused on determining the concept of academic responsibility, clarifying the correlation between the state of the academic freedom and academic responsibility, substantiation of the main approaches to their regulatory consolidation and including the academic responsibility into organizational and legal mechanism of ensuring academic freedom in terms of democratic, legal statehood. Research methods: a set of general and special methods of scientific knowledge - terminological, logical, semantic, functional, normative, comparative legal, and system-structural. Results: the definition of the concept of «academic responsibility» has been formulated, the main criteria for its distinguishing from other types of legal responsibility have been identified, and directions for further development of domestic legislation in the field of regulation of academic virtuous and academic responsibility have been outlined. The choice of criteria and indicators that promote a clear understanding of academic responsibility as an independent institute of sectoral legislation is substantiated. It is proved that academic responsibility in its content and from should meet the criteria of formal certainty, uniqueness and harmonization in the system of the effective legal regulation. Discussions: it was proposed to make the changes in the current legislation in terms of the normative consolidation of the concept of «academic responsibility», strict regulation of the types and measures of the state coercion for the violation of the relevant norms.